MOTIF KARYAWAN MENGKOMUNIKASIKAN POSITIVE ELECTRONIC WORD OF MOUTH (EWOM) DI SITUS JEJARING SOSIAL - Tisu, Rosadalima (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2022)
Abstract: Electronic word of mouth (eWOM) has become a concern for researchers in the marketing field in recent decades. Existing research explains the reasons consumers disclose eWOM on social media (Facebook), but the motivation for employee eWOM behavior is not focused on research. This article aims to find out what factors encourage employees to grow positive eWOM on social media (Facebook). Respondents as many as 115 employees were obtained from questionnaires distributed online. The results reveal that three variables have an effect on employee eWOM behavior, including task performance, branding benefits and other assistance, while other variables have no effect on employee eWOM behavior, namely impression management and social benefits. This study provides a theoretical contribution to the eWOM literature by integrating consumer eWOM and employee OCB research, this issue from an internal employee perspective. In addition, providing deep support for marketing managers motivates employees to create positive eWOM on social media (facebook) voluntarily. Â Abstrak: Electronic word of mouth (eWOM) menjadi perhatian bagi peneliti di bidang pemasaran dalam beberapa dekade ini. Penelitian yang ada menjelaskan alasan konsumen membeberkan eWOM di sosial media (Facebook), namun motivasi perilaku eWOM karyawan perusahaan tidak diteliti secara terfokus Artikel ini bertujuan untuk mencari faktor apa saja yang mendorong karyawan untuk menumbuhkan eWOM positif di Sosial media (Facebook). Responden sabanyak 115 orang karyawan didapat dari kuesioner yang disebarkan secara online. Hasilnya mengungkapkan tiga variabel berpengaruh terhadap perilaku eWOM karyawan antara lain task performance, branding benefits dan helping other sedangkan dua variabel tidak berpengaruh terhadap perilaku eWOM karyawan yaitu impression management dan social benefits. Studi ini memberikan sumbangan secara teori pada literatur eWOM dengan mengintegrasikan eWOM konsumen dan penelitian OCB karyawan, menyelidiki masalah ini dari perspektif karyawan internal. Selain itu, memberikan implikasi mendalam bagi manajer pemasaran memotivasi karyawan untuk membuat eWOM positif di sosial media (facebook) secara sukarela.